2005
DOI: 10.1111/j.1600-0722.2005.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries inhibition around composite restorations by pulsed carbon dioxide laser application

Abstract: This in vitro study aimed to evaluate whether laser irradiation of cavity margins reduces enamel demineralization around composite restoration. Enamel cavities were prepared in 33 human enamel slabs, which were randomly divided into three groups. One group was kept as a control, and the cavosurface margin of the cavities of the other groups were irradiated, using a CO(2) laser (lambda = 10.6 microm), at 8 J.cm(-2) or 16 J.cm(-2). The cavities were restored with a resin-based composite, according to the manufac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
31

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 33 publications
0
42
0
31
Order By: Relevance
“…Hossain et al 12 reported an increase in the calcium to phosphorus ratio achieved during laser irradiation, which leads to caries inhibition. 16,17 Therefore, laser irradiation might have an advantage as an etchant for orthodontic bonding. In previous studies [7][8][9] , cutting of enamel and dentine with laser systems was established.…”
Section: Discussionmentioning
confidence: 99%
“…Hossain et al 12 reported an increase in the calcium to phosphorus ratio achieved during laser irradiation, which leads to caries inhibition. 16,17 Therefore, laser irradiation might have an advantage as an etchant for orthodontic bonding. In previous studies [7][8][9] , cutting of enamel and dentine with laser systems was established.…”
Section: Discussionmentioning
confidence: 99%
“…27 Bu çürük koruyucu etki Ca:P oranındaki değiĢiklikler, karbonatın azalması ve pirofosfat oluĢumu ile iliĢkilendirilmiĢtir. 39 Asit ile pürüzlendirme sırasında diĢin tükürükten çok iyi izole edilmesi gerekirken, lazer ile pürüzlendirme su soğut-ması ile yapıldığından tükürük izolasyonu gerekmemektedir. Bu da tükürük izolasyonunun zor sağlandığı klinik durumlarda (çocuk hasta, posterior bölge diĢleri) teknik hassasiyetin az olması nedeni ile avantaj sağ-lamaktadır.…”
Section: Tartiġmaunclassified
“…Since then, several studies on caries prevention have been published due to the development of several types of lasers, such as CO 2 , (Stern & Sognnaes, 1972;Featherstone, et al, 1998;Hsu, et al, 2000;Tisai, et al, 2002;Kato, et al, 2003;Klein, et al, 2005;Steiner-Oliveira, et al, 2006), argon (Westerman, et al, 2002;Nammour, et al, 2005), Nd:YAG (Bahar & Tagomori, 1994;Hossain, et al, 2001a), and Diodo (Kato, et al, 2006) and more recently with the group of erbium lasers: Er, Cr:YSGG and Er:YAG (Kayano, et al, 1989;Fried, et al, 1996;Hossain, et al, 2001b;Apel, et al, 2004). There are various theories to explain the reduced acid solubility of dental enamel after heating.…”
Section: Laser and Caries Preventionmentioning
confidence: 99%